University social responsibility: a look from the student perception in the University Communal Work Empodero in the Atlantic Campus - Sojo Mora, Blanca Luz (2023)
In order to determine the sense of social responsibility acquired by university students at the end of the University Communal Work (TCU), a mixed investigation was carried out in which response frequencies given by the student body are described and quantified. There was a total participation of 26 students, each person carried out 300 hours of intervention in the community and once their contribution was finished, they completed a questionnaire. The main result was a change in the perception of the student body at the end of the TCU, showing greater awareness and commitment to social responsibility. In addition, it is evident that student participation in social projects such as the TCU during higher education allows them to know the existing social needs and assess possible contributions from their areas of study. It is concluded that the TCU contributes to the training of responsible professionals for the common good.